Factors associated with the choice of delivery place: A cross-sectional study in rural areas of Indonesia - Haerawati Idris (Belitung Nursing Journal, 2022)
Background: Developing countries, including Indonesia, commonly face maternal mortality as a public health concern, which needs special attention. Using maternal delivery services in health facilities may reduce maternal mortality. However, little is known about the general use of delivery services in health facilities in rural areas, Indonesia. Objective: This study aimed to analyze determinants in choosing delivery places in rural areas of Indonesia. Methods: A cross-sectional quantitative design with secondary data from the 2014 Indonesian Family Life Survey (IFLS) was used in this study. There were 2,389 mothers aged 15-49 years in rural areas were included. Data were analyzed using a logistic regression test. Results: It was found that 67% of mothers gave birth in health facilities. Tertiary and secondary education levels, residence in Java and Bali regions, economic status, insurance ownership, and job status were significantly related to the choice of delivery place in health facilities. Tertiary education was the most dominant factor correlated with the use of delivery services in health facilities (p < 0.001; PR = 4.55; 95% CI = 3.751-5.542). Conclusion: Education is the key factor associated with the choice of delivery place. Therefore, it is suggested that the government and healthcare workers, especially nurses and midwives, improve mothers’ education and provide strategies to increase knowledge in choosing delivery services to enhance their health outcomes.